Contributions of Javanese Scholars towards the enrichment of the Malay intellectual Heritage = Sumbangan para ulama Jawa terhadap pengayaan Warisan Intelek Melayu - Yakob, Abdul Ghani (International Islamic University Malaysia, 2015)

(untitled)
This study highlights the contributions of Javanese scholars towards the enrichment of the intellectual heritage in the Malay Archipelago. Such a study in Arabic is rare despite the long historical relations between the region and the Arab/Muslim world. The study concludes that with the beginning of the twentieth century a number of Javanese scholars studied from the highly-ranked scholars in the Holy Ka‘bah, including Sheikh DÉ’Ëd bin ‘Abd Allah al-PatÉnÊ, the leader of the Patani community in Makkah. They sought authentic Islamic learning and wrote scientific works in Arabic and Jawi. They served as a bridge between the Middle East and Far East throughout the Islamic era. After having secured Islamic and Arabic learning, they returned to their country and established Islamic educational institutions, private and public, as a means to spread knowledge of Islam.